DIAGNOSTIC TEST INSTRUMENTS FOR THE BASIS OF REMEDIAL LEARNING - Deni Iriyadi (LPPM Universitas Negeri Jakarta, 2021)
his research is a type of development research that is focused on developing a diagnostic test instrument to see students' conceptions. The research was conducted at SMA Negeri 1 Watampoen in class X. This research regulates the stage of developing an instrument consisting of 6 steps: (1) determining the specifications of the instrument, (2) determining the domain of the instrument, (3) determining whether the format is open-ended or closed ones to be used, (4) determining the test / instrument format, (5) determining whether the instrument is used for groups or individuals, (6) determining the length of the instrument. From this study, one third of the diagnostic tests were obtained which consisted of testing, examination format, and error checking. Giving remedials to students should not be done just like that without taking into account the knowledge that students have. By using a diagnostic test, students' understanding can be identified including what material they do not understand. This can be used as a reference for providing improvements to students